2006
DOI: 10.1016/j.jemermed.2005.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Viral load and outcome in SARS infection: The role of personal protective equipment in the emergency department

Abstract: This study was conducted to evaluate the effectiveness of personal protective equipment (PPE) against severe acute respiratory syndrome (SARS). Sixteen patients in a SARS cluster, including 4 health care workers (HCWs) and 12 non-HCWs were studied. We compared the initial viral load by nasopharyngeal swabs, clinical progression, and outcome of this cluster. The HCWs had a lower viral load. The non-HCWs had a higher mean C-reactive protein, lower oxygen saturation, and a higher incidence of intubation and death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Finally, there are likely to be difficulties in ensuring compliance in healthcare workers [35]. Nevertheless personal protective equipment has led to major improvements in general infection control procedures in the hospital setting [36][37][38] and should not be discounted due to the lack of available data examining influenza virus outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are likely to be difficulties in ensuring compliance in healthcare workers [35]. Nevertheless personal protective equipment has led to major improvements in general infection control procedures in the hospital setting [36][37][38] and should not be discounted due to the lack of available data examining influenza virus outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Case control studies during the 2003 SARS crisis suggested that N95 respirators may be somewhat more protective than surgical masks against the SARS coronavirus. [31][32][33][34][35] More recently, a direct comparison of N95s to surgical masks found that surgical masks were not inferior to N95 respirators at protecting HCWs against influenza. 36 Unfortunately, this trial was terminated prematurely, limiting its power to detect differences in effectiveness, because of regulations pertaining to the 2009 H1N1 influenza pandemic.…”
Section: Health Care Workers' Views About Respirator Use and Featuresmentioning
confidence: 99%
“…Another study on SARS illustrated that the surgical and N95 masks were both effective in significantly reducing the risk of infection 8 ; however, did not confer 100% protection against infection but supported that it may reduce the initial degree of exposure to the virus. 9 Similarly, for swine flu, routine use of surgical masks along with hand hygiene has been identified to be of use in all clinical settings in dropping the risk of infection. However, it also observed that the use of such PPEs doesn't confer 100% protection against SARS.…”
Section: Introductionmentioning
confidence: 99%
“…However, it also observed that the use of such PPEs doesn't confer 100% protection against SARS. 9 It is also indicated that improper use of PPEs even among medical care workers as well the general population leads to an increase in risk for COVID-19 and contributes to the transmission of pathogens. 10 …”
Section: Introductionmentioning
confidence: 99%